Real-world therapy with pembrolizumab: outcomes and surrogate endpoints for predicting survival in advanced melanoma patients in Germany - Mohr, Peter; Scherrer, Emilie; Assaf, Chalid; Bender, Marc; Berking, Carola; Chandwani, Sheenu; Eigentler, Thomas; Grimmelmann, Imke; Gutzmer, Ralf; Haferkamp, Sebastian; Hassel, Jessica C.; Hauschild, Axel; et al. (Cancers, 2022)
Knowledge on the real-world characteristics and outcomes of pembrolizumab-treated advanced melanoma patients in Germany and on the value of different real-world endpoints as surrogates for overall survival (OS) is limited. A sample of 664 pembrolizumab-treated patients with advanced melanoma from the German registry ADOReg was used. We examined OS, real-world progression-free survival (rwPFS), real-world time to next treatment (rwTtNT), and real-world time on treatment (rwToT). Spearman’s rank and iterative multiple imputation (IMI)-based correlation coefficients were computed between the OS and the rwPFS, rwTtNT, and rwToT and reported for the first line of therapy and the overall sample. The median OS was 30.5 (95%CI 25.0-35.4) months, the rwPFS was 3.9 months (95%CI 3.5-4.9), the rwTtNT was 10.7 months (95%CI 9.0-12.9), and the rwToT was 6.2 months (95%CI 5.1-6.8). The rwTtNT showed the highest correlation with the OS based on the IMI (rIMI = 0.83), Spearman rank correlations (rs = 0.74), followed by the rwToT (rIMI = 0.74 and rs = 0.65) and rwPFS (rIMI = 0.69 and rs = 0.56). The estimates for the outcomes and correlations were similar for the overall sample and those in first-line therapy. The median OS was higher compared to recent real-world studies, supporting the effectiveness of pembrolizumab in regular clinical practice. The rwTtNT may be a valuable OS surrogate, considering the highest correlation was observed with the OS among the investigated real-world endpoints.